Ciptagelar village identification in the documentary film ''Pare” - Hardi Ibrahim; Erik Muhammad Pauhrizi; Gharisa Nur Alam (Cinematology: Journal Anthology of Film and Television Studies, 2021)
In Indonesia, rice is one of the main commodities cultivated in the agricultural sector. Rice is also a staple food commodity in Indonesia. Rice also has a vital position in the economic sector, and is the lifeblood of the rural economy. Rice has deep philosophical value for the people of Kasepuhan Ciptagelar, the rice produced by Kasepuhan Ciptagelar cannot be sold. The Kasepuhan Ciptagelar community considers rice to be the embodiment of Dewi Sri, Dewi Sri herself according to the Kasepuhan Ciptagelar community is the giver of life, therefore the customary law of Kasepuhan Ciptagelar prohibits selling rice because selling rice is the same as selling oneself and this is a category of great sin for the Kasepuhan community. Ciptatitle. However, because of their compliance with this customary law, they can meet their food needs independently. This study aims to examine rice culture in the Kasepuhan Ciptagelar community by looking at the causes of the Kasepuhan Ciptagelar community worshiping rice and the consequences of customary law that prohibits the Kasepuhan Ciptagelar community from selling rice and implemented into the design of documentary films. The research approach in this study uses a qualitative research model, using an ethnographic approach then combined with a base research design method as the stage of creating a documentary film. Ethnography aims to unravel culture as a whole, both material and abstract. The results of the study show how the continuity of indigenous peoples in Kasepuhan Ciptagelar is seen from the community's obedience to customary law or carrying out ancestral teachings that regulate rice cultivation until its distribution can meet their food needs. The implications of this research can be a reference for modern society in treating the universe for food security. Keywords — Ciptagelar; Documentary film; Customary law; Food security; Culture